DESIGNING AND MANUFACTURING THE CORRELATOR AND DECORRELATOR SIMULATIONS - Ani Sulistyowati; Raida Tri W; Yoedy Moegiharto (SAINTEKBU, 2008)
Recently the CDMA communication system has been developed with an ability to keep the secret of the transmitted information and also immune to  interferences.            In a CDMA system every user has an identification code which are mutually independent (orthogonal). To prove the orthogonality of the codes the  correlation process is used.            In this final project, we simulate the correlation process by using the Hadamard-Walsh matrix codes. The correlation process that is used to prove the orthogonality will apply the XNOR calculation. The correlation processes consist of two i.e. autocorrelation and crosscorrelation in which autocorrelation process will always result in correlation coefficient that is larger than the crosscorrelation process.